PENGARUH MOTIVASI KERJA DAN LINGKUNGAN KERJA FISIK TERHADAP KINERJA KARYAWAN PADA PT HYUNDAI SERPONG TANGERANG SELATAN - Adinda, Avrillia; Agrasadya, Agrasadya (JURNAL RUMPUN MANAJEMEN DAN EKONOMI, 2025)
This study aims to find out how work motivation and physical work environment affect employee performance at PT Hyundai Serpong South Tangerang, either partially or simultaneously. The method used in this study is the quantitative method. A population of 60 employees with a sample determination using a saturated sampling technique obtained 60 samples. The data was used through observation techniques, questionnaires and documentation. The analysis methods used in this study were validity test, reliability test, classical assumption test, multiple linear regression analysis, determination test and significant test (t test and F test). The results of the study were obtained as a partial result that work motivation has a positive and significant effect on employee performance, this can be seen from the t-test with a t-test of 19.467 > ttable 2.002 and Sig. 0.000 < 0.05. Partially, the physical work environment has a positive and significant effect on employee performance, this can be seen from the t-test with a t-test with a tcal value of 10.147 > ttable 2.002 and Sig. 0.000 < 0.05. Simultaneously, work motivation and physical work environment have a positive and significant effect on employee performance, this can be seen from the results of the F test with Fcount 200.635 > Ftable 3.16 and Sig. 0.000 < 0.05, multiple linear regression obtained the equation Y=3.837+0.784X1+0.131X2 with a multiple correlation coefficient of 0.936.